Fostering Entrepreneurship in Georgia - Kuriakose, Smita (Washington, DC: World Bank, 2013)
Job creation and productivity growth are at the forefront of today's global development agenda. The 2013 world development report on jobs identified entrepreneurship as an important tool in addressing these dual goals. This study uses the entrepreneurship model put forth in the organization for Economic Co-operation and Development (OECD)-Eurostat Entrepreneurship Indicator Program (2009), with minor modifications. The model comprises various determinants that policy can affect and that in turn influence entrepreneurial performance, or the amount and type of entrepreneurship that take place. The model then refers to the impact of entrepreneurship on higher-level goals such as economic growth, job creation, and poverty reduction. This study focuses on determining the level of entrepreneurship in Georgia and analyzes the role of each determinant in both fostering and constraining entrepreneurial activity. Entrepreneurs view opportunities in the economy by measuring their profit-making potential; that is their first motivation. Entrepreneurs will not pursue a societal need unless they can successfully make a profit. Entrepreneurship also depends on various social and individual characteristics of gender and culture. It involves taking risks, and potential entrepreneurs cannot be risk-averse. A fundamental question stemming from analyzing these determinants of entrepreneurship is how to design effective public policy that promotes innovative firm creation and enables existing firms to catch up, improve productivity, and grow. Experiences from Asian countries and developed economies have shown that innovative Small Medium Enterprises (SMEs) and knowledge-based firm creation have played a major role in the development of new national economic advantages. In this context public policy is pivotal in creating an enabling environment that helps alleviate the market failures that inhibit firm growth. Emerging markets have other environmental conditions that are not present (or are less prevalent) in developed markets, and investors considering investing in emerging markets will face added risk as a result.